1998
DOI: 10.1007/s003300050509
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging and MR angiography in popliteal artery entrapment syndrome

Abstract: Popliteal artery entrapment (PAE) syndrome is an uncommon congenital anomaly seen in young adults causing ischemic symptoms in the lower extremities. It is the result of various types of anomalous relationships between the popliteal artery and the neighboring muscular structures. The purpose of this study was to define the role of MR imaging combined with MR angiography in the diagnosis of PAE cases. Four cases with segmental occlusion and medial displacement of popliteal artery in digital subtraction angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…Magnetic resonance imaging is reported as the diagnostic method of choice when there is clinical evidence or duplex Doppler imaging suggestive of PAES. 6 Recurrent external compression of the popliteal artery leads to mechanical damage to the vessel wall. This damage occurs in three distinct histological stages.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging is reported as the diagnostic method of choice when there is clinical evidence or duplex Doppler imaging suggestive of PAES. 6 Recurrent external compression of the popliteal artery leads to mechanical damage to the vessel wall. This damage occurs in three distinct histological stages.…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography may reveal stenosis of the popliteal artery and, more importantly, may delineate the anatomy of adjacent structures in the popliteal fossa [43]. MRI most accurately enables the evaluation of popliteal fossa anatomy and entrapment of vessel without the need for an iodinated contrast agent or radiation exposure [44]. Transverse T1-weighted MRI sequences typically demonstrate deviation of the popliteal artery and the abnormal local anatomy of the popliteal fossa.…”
Section: Treatment Of Cacsmentioning
confidence: 98%
“…MR imaging combined with MR angiography is the ideal imaging method for diagnosing arterial compression. It enables to locate the arterial stenosis as well as the anatomical relations between the artery and the adjacent muscle [ 26 ]. It has been demonstrated that stress MR imaging can improve the diagnosis of popliteal entrapment syndrome [ 27 ].…”
Section: Artery Entrapment Syndromementioning
confidence: 99%